Py2UML: a Tool for Visually Impaired Students to Build UML Diagrams from Python Coding - Verde, Alisson; Alves, Lais; Fraga, Lucas; Soares, Larissa (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
The inclusion of individuals with disabilities in quality education ensures both access and permanence of these students in education. Thus, they can compete for opportunities more equally. To allow students with disabilities to enter higher education institutions, efficient inclusive public policies are needed. However, this is not enough to guarantee their permanence. Visually impaired students from Information and Communications Technology (ICT) and Computer Science fields may have serious difficulties with visual content within computing teaching. Professors need to keep a closer eye and look for other ways and tools that support them during their learning. For example, it can be challenging to explain UML diagramming to someone who cannot see. Even more challenging can be the construction of UML diagrams using non-accessible tools. This work presents Py2UML, a web system easily accessible by screen reader that allows visually impaired people to write diagrams through Python programming. We hope that Py2UML can contribute to building a more inclusive learning environment. Link: https://www.youtube.com/watch?v=8IzOVcqsjEQ